(untitled) (Fiep Bulletin - online, 2014)
In this paper we present summarizing of views of the authors dealing with the issue of the quality of life of adolescents. The solution is differentiated with respect to various aspects and areas of life, with different views and attitudes of experts on the topic. In addition, we point out even further the possibility of the sample survey using a questionnaire SQU ALA and methods of evaluation. The contribution is part of a grant project KE GA no. 014UKF -4/2013, titled: „Improving the quality and level of health of adolescents by means of physical activity in primary and secondary schools“. QUALITY OF LIFE IN ADOLESCENTS